Playful haptic environment for engaging visually impaired learners with geometric shapes - Petridou, Maria (2014)
This thesis asserts that modern developments in technology have not been used as extensively as they could to aid blind people in their learning objectives. The same could also be said of many aspects of other areas of their lives. In particular in many countries blind students are discouraged from learning mathematics because of the intrinsically visual nature of many of the topics and particularly geometry. For many young people mathematics is also not a subject that is easily or willingly tackled. The research presented here has thus sort to answer whether a playful haptic environment could be developed which would be attractive to blind users to learn and interact with geometric concepts. In the study a software tool using a haptic interface was developed with certain playful characteristics. The environment developed sought to give the blind users practice in interacting with three dimensional geometric shapes and the investigation of the size of these shapes and their cross-section. The playful elements were enhanced by adding elements of competition such as scores and time limits which promote competition between the users. The tests have shown that blind users can easily use the system to learn about three dimensional shapes and that practice increases their confidence in recognising shape and size of these objects.